(untitled) (Journal of Nepalese Business Studies, 2021)
This study aims to analyze the competitive conditions of commercial banks in Nepal. Competition is measured through structural and non-structural measures of bank competition. Data were taken from 21 commercial banks of Nepal using pooled sampling method, including five commercial banks based on the highest total assets and sixteen commercial banks using random sampling. Concentration ratio, Herfindahl-Hirschman Index, H-statistic and Lerner Index measures were used to assess the competitive position of Nepalese commercial banks. Panel data regression model with bank fixed effect and time fixed effect was employed to measure H-statistic and Lerner index. Findings showed the increasing pattern of capitalization and the decreasing trend of non-performing loan ratio, indicating that Nepalese commercial banks have a low possibility of loan default and, are more financially stable. It also showed the declining trend of bank concentration and HHI, suggesting that Nepalese commercial banks are losing their monopoly power and becoming more competitive in recent years. Competition in the loan market was found higher than deposit market competition. Banks have to pay special attention to loan portfolio management rather than deposit collection strategies. This study concludes that the competitive condition of Nepalese commercial banks is monopolistic. Therefore, appropriate strategies might be taken into action to sell financial products and services competitively.